2018
DOI: 10.3389/fmicb.2018.02381
|View full text |Cite
|
Sign up to set email alerts
|

How Rainforest Conversion to Agricultural Systems in Sumatra (Indonesia) Affects Active Soil Bacterial Communities

Abstract: Palm oil production in Indonesia increased constantly over the last decades, which led to massive deforestation, especially on Sumatra island. The ongoing conversion of rainforest to agricultural systems results in high biodiversity loss. Here, we present the first RNA-based study on the effects of rainforest transformation to rubber and oil palm plantations in Indonesia for the active soil bacterial communities. For this purpose, bacterial communities of three different converted systems (jungle rubber, rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 103 publications
(139 reference statements)
11
37
1
Order By: Relevance
“…The soil microbial community composition changed in the converted land use systems compared to rainforest with similar trends as in previous studies targeting these sampling sites [9,15,16]. Proteobacteria were negatively and Acidobacteria positively affected by rainforest conversion.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The soil microbial community composition changed in the converted land use systems compared to rainforest with similar trends as in previous studies targeting these sampling sites [9,15,16]. Proteobacteria were negatively and Acidobacteria positively affected by rainforest conversion.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, microorganisms play a key role in decomposing soil organic matter and mineralizing nutrients in soil [7]. It has been shown that rainforest conversion to plantations has negative effects on the biodiversity of fungi [8,9], protists [10], vertebrates [11], insects and plants [12][13][14], archaea [15], but not on bacterial diversity which increased [15,16]. Additionally, the microbial community composition was severely affected by these conversion processes with a high impact on Proteobacteria which showed an abundance decrease and Actinobacteria, which showed an abundance increase with increasing land use intensity [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations